(untitled) (The Journal of Economic Concerns, 2024)
E-commerce has revolutionized the global shopping landscape, especially among younger generations, by providing unprecedented convenience and accessibility. This shift has transformed traditional retail, enabling consumers to easily find, compare, and purchase products online. The internet has created a centralized platform that brings together competitors and consumers, opening new avenues for product and service promotion. Customer relationships are crucial in customer focused marketing, with Customer Relationship Management (CRM) leveraging customer data to enhance promotions. The evolution from e-CRM to CRM highlights the growing emphasis on customer relationships to establish competitive power. This study investigates the impact of trust, privacy, reliability, responsiveness, and customer satisfaction on the success of electronic customer relationship management (E-CRM) systems in the Nepalese insurance sector. Based on primary data from 393 respondents in the Nepalese insurance sector, the study employs descriptive statistics, correlations, and regression analysis. Data are collected using Google Forms The results show that privacy, reliability, responsiveness, trust, and customer satisfaction are positively correlated with the success of E-CRM systems. Higher levels of these factors lead to greater success in E-CRM systems within the Nepalese insurance sector.